Church, State and Colonialism in Southeastern Congo, 1890–1962 - Loffman, Reuben A. (Cambridge Imperial and Post-Colonial Studies Series, 2019)
1 Introduction: The Catholic 'Republic' in Southeastern Congo -- 2 Pre-Colonial Politics in Kongolo to 1890 -- 3 The Halting Development of Catholic Power in Kongolo, 1891-1917 -- 4 The Failure of ‘Great’ Chieftainships and the Extension of Catholic Authority, 1918-1932 -- 5 Missionaries and the Formation of Colonial Chieftainship, 1933-1939 -- 6 A Marriage of Convenience: Church and State in the Late Colonial Period, 1940-1956 -- 7 Religion, Class and the Katangese Secession, 1957-1962 -- 8 Conclusion --